Civil society and women's NGOs in Serbia - Vuković, Ana S. (Collection of Papers of the Faculty of Philosophy in Priština, 2015)
In the paper we examine the position of civil society in Serbia, particularly women's NGOs. In the first part of the paper author will point out the concept and development of the concept of non-governmental organizations as well as the position and problems of civil society in Serbia. In the second part of the paper the author deals with the emergence and development of women's organizations and points out some problems in their work within civil society. In this section, we will point out the important information from the researches of women's NGOs in Serbia. The first outlines of the functioning of civil society in Serbia appeared in the late 19th and early 20th century. Much later, during the nineties of the 20th century, the establishment of non-governmental organizations stemmed from the need to create a social bloc that will confront the regime's block and through whose functioning citizens will exercise the rights and fulfill the needs that could not be met through state institutions. The civil sector has a long but not cherished tradition in our society, some civil society organizations are stigmatized in public because of their compromising positions, and the importance and meaning of their actions is often denied. Thus, in connection with the activities of non-governmental organizations are appearing numerous stereotypes. According to some stereotypes, which are especially important and intensified during the nineties, NGOs because of the way funding (mainly from foreign funds) and their non-institutional functioning  had negative image in society. To improve the civil sector in a society it is necessary that the tradition of the civil organization fosters, through clear legal framework established by the state, more representation of the organizations in media and that their activities would provide to all citizens information about a role, forms, action and a need for civil society organizations to exist. Women's organizations are civil society organizations because their work is focused for the good of its members and the general public uses and because they engage in activities of common interest which are considered as an important feature of civil society organizations. In the last decade, and especially today, one of the most important factors for survival of women's organizations and other forms of civil action is possibility of funding. Problems in the functioning of women's groups and organizations are visible, the problem of their survival due to stricter criteria for obtaining new grants for projects, then determine priorities (and character designs) and other requirements that burden all non-governmental organizations and narrows the space for their actions. Another problem illustrates the concept of the internal modes and forms of women's groups and organizations among the activists. Civil society should have a significant impact on positive social change, because the organizations of civil society are often the first detectors of certain social problems and those who are first confronted with problems and try to solve them. Regardless of the development of a country it is important that civil society organizations exist and act in continuity, in times of crisis and in periods of social calm, although social climate is not always suitable for their work. To the extent that civil society organizations are managed to establish some sort of balance between its primary objectives to meet the specific needs of citizens, state interference in their actions, and requires from foreign donors so far they will justify their social role. Of course, it involves skill of OCD members to coordinate multiple demands and actively and continuously do their work in society. Active engagement of civil society is not always easy, and a lot of organizations have to align their work with the needs of "the market" in terms of their compliance with rules for participation in competitions of which is directly dependent the survival of the organization. Also, it is important to establish and maintain cooperation between civil society organizations and the exchange of experiences, which is challenging due to mutual competition for the provision of finance, but this cooperation is not necessarily impossible. This is particularly important in the case of women's organizations, that regardless of the type of activity (education, combating violence against women, etc.) have one and same target group - women in society. Unfortunately, on the basis of results of this research we can conclude that NGOs and particularly women's organizations have not yet been recognized as very important in society. Given the initial enthusiasm and despite all the obstacles in the work of NGOs in the nineties and over the next few years after 2000, for the OCD will be a real challenge to survive in the current social climate of economic hardship and reduced cash flow from domestic and foreign funds. It will take great resourcefulness of civil organizations to "jump in" and continue to fill the empty space towards better solving social problems.
Keywords: gender studies; attitudes about civil society organizations; gender equality; social activism